PERBEDAAN AKTIVITAS BELAJAR GEOGRAFI ANTARA SISWA KELAS XI KELOMPOK PEMINATAN DENGAN LINTAS MINAT DI SMA NEGERI 1 NAN SABARIS - Iwana Putri Rinjani; Rahmanelli Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This study aims to analyze and describe (1) geography learning activities in class XI students with specialization groups and cross-interest groups at SMAN 1 Nan Sabaris, (2) differences in student geography learning activities between class XI specialization groups and cross-interest groups at SMAN 1 Nan Sabaris . This research method uses a descriptive method with a quantitative approach. Determination of the sample was taken using a purposive sampling technique. Data was collected using observation sheets. Data analysis used descriptive analysis and Independent Sample T-Test. The results of the study showed: (1) the geography learning activities of class XI specialization group students were in the medium category (67.05%) and the geography learning activities for class XI the cross-interest group were in the high category (70.26%), (2) the level of activity specialization group learning is lower than the cross-interest group and shows a sig value of 0.404. This means that there is no significant difference in Geography learning activities between class XI students in the specialization group with cross-interest groups at SMAN 1 Nan Sabaris.